Economic Burden Bore by Patients and Families because of stroke: Policy Assessment - Fadhilah, Honesty; Permanasari, Vetty Yulianty (Journal of Indonesian Health Policy and Administration, 2020)
Stroke to this day is still a disease that causes a high disability. In the future, it will require a prohibitive cost so that it has an impact on the socio-economic consequences for patients and their families. The price is prohibitive so that the impact on socioeconomic implications for patients and their families. Because of that, the purpose of the study is to estimate the cause of the cost that causes an economic burden from a stroke. The method that is used is a content analysis by doing a further literature review from various sources, from journal to textbook from a national level to international. Literature studies show that direct medical cost, which is rehabilitation, and nursing care cost is identified as the leading contributor to the high price of economic burden from a stroke. High costs incurred cause family to experience catastrophic financial disaster; it even impacts to drop welfare level. Social preventive action is needed to reduce the high prevalence of stroke to reduce the cost, to protect every household from financial disaster from a stroke.